Perinatal period cytokines related to increased risk of future allergy development - Žižka, Jan; Kverka, Miloslav; Novotná, Olga; Staňková, Irena; Žádníková, Raja; Kocourková, Ingrid; Šterzl, Ivan; Prokešová, Ludmila (Folia microbiologica, 2007)
Testing of cytokine levels in colostrum, cord blood and amniotic fluid of healthy and allergic mothers and their newborns (using protein microarrays and quantitative analysis by ELISA) revealed differences in the levels of IL-5, IL-10, TGF-beta, TNF-alpha, EGF and eotaxin between healthy and allergic groups. Significantly higher concentration of IL-5 and IL-10 in the colostrum of allergic mothers and cord blood of their children and also tendency to a higher level of IL-4 found at allergic mothers and their children (but without statistical significance) indicate a bias to T(H)2 response in this group. The higher level of TGF-beta in the colostrum of healthy mothers should be involved in beneficial immunological tuning of their children including enhanced IgA formation and better intestine maturation. In amniotic fluid, concentration of TGF-beta was higher in children of allergic mothers. A significantly higher level of EGF was proved in the colostrum of healthy mothers and in cord blood of their children in comparison with allergic group. EGF deficiency in the allergic group could impair or delay intestine maturation and support thus allergy development.
Keywords: Research Support as Topic; alergie; Humans; TNF-alfa; prognóza; lidé; Epidermal Growth Factor; kolostrum; Colostrum; Infant, Newborn; Cytokines; Tumor Necrosis Factor-alpha; Prognosis; rizikové faktory; Enzyme-Linked Immunosorbent Assay; Mothers; cytokiny; Risk Factors; Hypersensitivity; novorozenec; ELISA; plodová voda; finanční podpora výzkumu jako téma; epidermální růstový faktor; Amniotic Fluid; matky